Last Glacial Maximum precipitation pattern in the Alps inferred from glacier modelling - Becker, Patrick; Seguinot, Julien; Jouvet, Guillaume; Funk, Martin (Geographica Helvetica, 2016)
During the Last Glacial Maximum (LGM), glaciers in the Alps reached a maximum extent, and broad sections of the foreland were covered by ice. In this study, we simulated the alpine ice cap using a glacier flow model to constrain the prevailing precipitation pattern with a geomorphological reconstruction of ice extent. For this purpose we forced the model using different temperature cooling and precipitation reduction factors. The use of the present-day precipitation pattern led to a systematic overestimation of the ice cover on the northern part of the Alps relative to the southern part. To reproduce the LGM ice cap, a more severe decrease in precipitation in the north than in the south was required. This result supports a southwesterly advection of atmospheric moisture to the Alps, sustained by a southward shift of the North Atlantic storm track during the LGM.